Saving Tiger, Orangutan & Co: how subjective knowledge and text complexity influence online information seeking and behavior - Schmitt, Josephine B.; Schneider, Frank M.; Weinmann, Carina; Roth, Franziska S. (Information, communication & society, 2019)
Besides others, subjective knowledge ‒ the feeling of being knowledgeable ‒ as well as the complexity of a communicated content have been shown to have an impact on different behavioral outcomes ‒ also in the field of consumer choices. However, it remains open how both factors influence subsequent outcomes such as information seeking, behavioral intentions, or actual choice behavior ‒ especially related to environmental issues. With a 2 (high/low subjective knowledge) × 2 (high/low complex information) between-subjects design (N = 87), we investigated the effects of subjective knowledge and complexity of an online news text about a specific environmental topic (i.e., palm oil) on behavioral intentions, online information seeking as well as on behavioral choices. Higher subjective knowledge raised the probability to volunteer for an NGO and the duration of time spent on a palm oil-related webpage. Environmental attitudes determined the general likelihood to engage in palm oil-related web search and the number of webpages visited. Text complexity did not influence the target variables.